Switzerland ad her industries : (Swiss Office for The Development of Trade Zurich and Lausanne, 1948)
This book introduce the facts about Switzerland and her Natinal economy. Switzerland's economic relations with world markets. What Switzerland produc. The tourist trade and ecducation.